Pengaruh Rekrutmen dan Motivasi Kerja Terhadap Kinerja Karyawan pada PT Panca Persada Medika - Fauzan, Ahmad Arkan; Muhtadin, Imam (Otonomi, 2025)
This study examines the influence of recruitment and work motivation on employee performance at PT Panca Persada Medika. The research aims to determine the relationship between th ese variables and employee performance using a quantitative method with an associative approach. The study involved 50 employees using a saturated sampling method, with data collected through questionnaires. The analysis included reliability and validity tests, classical assumption tests, multiple linear regression analysis, and hypothesis testing. The results show that recruitment has a positive and significant effect on employee performance, as indicated by t-value > t-table (2.670 > 2.011) and significance 0.010 < 0.05. Work motivation also has a positive and significant effect, with t-value > t-table (6.766 > 2.011) and significance 0.000 < 0.05. Simultaneously, recruitment and work motivation influence employee performance, evidenced by an F-value of 108.396 > F-table 3.20 and significance 0.000. These two variables account for 82.2% of the variation in employee performance, while the remaining 17.8% is influenced by other factors. The findings emphasize the importance of optimizing the recruitment process and enhancing work motivation to improve employee performance.